Effect of Games and Sports on Academic Performance of Pupils in Primary Schools of Kigarama Sub-County Sheema District. - Arinaitwe, Daltone (Kabale University, 2025)
Man is a motor being. His life is characterized by a lot of deliberate movements like running, walking, jumping, catching, stretching, curling, balancing, pushing, pulling kicking, etc. These activities are natural to man’s life and evidently make his life flow. Studies of these physical activities in man have shown they are cardinal to his physical health intellectual development, talent building, social relations, positive use of leisure time, and longevity of life. They are also therapeutical to some illnesses and diseases such as cardiovascular diseases, hypertension, stress, stroke, kyphosis, and lordosis among others, all of which would reduce national medical bills. Farley Thomas (1976). It’s for these reasons that civilized societies have identified these games and sports in the form of exercises and sports and programmed them in their education curriculum, health clubs, and organized competitions. This study was set to examine the effect of games and sports on the academic performance of pupils in primary schools of Kigarama Sub-county, Sheema District. Games and sports were the independent variable whereas the academic performance of pupils was the independent variable. The study was guided by the following objectives; (i) To assess the level of participation of pupils in games and sports in Kigarama Sub-county. (ii) To establish the factors that affect participation in games and sports activities in the Kigarama sub-county. (iii) To ascertain the effects of games and sports on pupils’ academic performance in Kigarama Sub-county. The subjects of the examination included the pupils, teachers, and headteachers. The tools for data collection included a questionnaire which was served to the teachers and headteachers whereas the interview guides were served to the pupils. This study involved a sample population of 5 primary schools randomly selected but including all categories of schools i.e. public, private, mixed ones, day and boarding schools. There were 75 pupils sampled, 40 teachers and 5 headteachers from the sample schools who were served with interview guides and questionnaires respectively. The data collected was converted to percentages and presented in graphs and tables.